2017
DOI: 10.1111/2041-210x.12938
|View full text |Cite
|
Sign up to set email alerts
|

Using multi‐response models to investigate pathogen coinfections across scales: Insights from emerging diseases of amphibians

Abstract: Summary Associations among parasites affect many aspects of host-parasite dynamics, but a lack of analytical tools has limited investigations of parasite correlations in observational data that are often nested across spatial and biological scales.Here we illustrate how hierarchical, multiresponse modeling can characterize parasite associations by allowing for hierarchical structuring, offering estimates of uncertainty, and incorporating correlational model structures. After introducing the general approach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…Given that immune responses are costly and can be traded off with other demanding processes, such as reproduction and growth (Lochmiller and Deerenberg 2000), mounting an immune response sufficient to combat both of these parasites could have been beyond the resource capacity of our hosts. Field studies have found that Ranavirus and Bd are not associated with each other at the site (Olori et al 2018, Stutz et al 2018) or individual level, but there are positive associations between these parasites at the species level for some of the sampled amphibian species (Stutz et al 2018). Despite this, co-infections with Bd and Ranavirus, are common in nature (Whitfield et al 2013, Warne et al 2016, Watters et al 2018) and our findings suggest that these co-infections can be facilitative and thus appear to put host populations at greater risk than single infections.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given that immune responses are costly and can be traded off with other demanding processes, such as reproduction and growth (Lochmiller and Deerenberg 2000), mounting an immune response sufficient to combat both of these parasites could have been beyond the resource capacity of our hosts. Field studies have found that Ranavirus and Bd are not associated with each other at the site (Olori et al 2018, Stutz et al 2018) or individual level, but there are positive associations between these parasites at the species level for some of the sampled amphibian species (Stutz et al 2018). Despite this, co-infections with Bd and Ranavirus, are common in nature (Whitfield et al 2013, Warne et al 2016, Watters et al 2018) and our findings suggest that these co-infections can be facilitative and thus appear to put host populations at greater risk than single infections.…”
Section: Discussionmentioning
confidence: 97%
“…This nematode is a common parasite of amphibians in the Southeastern US and Latin America (Baker 1987, Vhora and Bolek 2013, Ortega et al 2015). Importantly, parasitic worms, Bd, and Ranaviruses are known to co-occur in amphibian hosts in the field (Hoverman et al 2012, Stutz et al 2018, Watters et al 2018). In the Peruvian Andes, an amphibian biodiversity hotspot, up to 50% of frogs were coinfected with Bd and Ranavirus (Warne et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other landscape-level influences on amphibian population dynamics include habitat degradation, pathogen presence, and chemical exposure. Interactions between parasite occurrence, habitat degradation, and chemical exposure introduce further complications in assessment of vulnerability (Koprivinkar and Redfern 2012;Stutz et al 2017) with the potential for agrochemicals to reduce immunity to parasite infection (Kiesecker 2002;Rohr et al 2008) and decrease parasite survival (Hua et al 2016). Multiple parasites do not always produce synergistic effects; compensatory effects of coinfection are also possible (Wuerthner et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Detecting associations between pathogens is also likely to depend on taxonomic and spatial scales that are seldom considered (Araújo & Rozenfeld ; Stutz et al . ). Studies commonly aggregate pathogen data to genus level, but associations between pathogens can be subtype or genotype‐specific (e.g.…”
Section: Introductionmentioning
confidence: 97%